The Homeodomain Transcription Factor NKX3.1 Modulates Bladder Outlet Obstruction Induced Fibrosis in Mice - Patel, Mehul S.; Bowen, Diana K.; Tassone, Nicholas M.; Gould, Andrew D.; Kochan, Kirsten S.; Firmiss, Paula R.; Kukulka, Natalie A.; Devine, Megan Y.; Li, Belinda; Gong, Edward M.; Dettman, Robert W. (Frontiers in Pediatrics, 2019)
Fibrosis is an irreversible remodeling process characterized by the deposition of collagen in the extracellular matrix of various organs through a variety of pathologies in children, leading to the stiffening of healthy tissues and organ dysfunction. Despite the prevalence of fibrotic disease in children, large gaps exist in our understanding of the mechanisms that lead to fibrosis, and there are currently no therapies to treat or reverse it. We previously observed that castration significantly reduces fibrosis in the bladders of male mice that have been partially obstructed. Here, we investigated if the expression of androgen response genes were altered in mouse bladders after partial bladder outlet obstruction (PO). Using a QPCR microarray and QRTPCR we found that PO was sufficient to increase expression of the androgen response gene Nkx3.1. Consistent with this was an increase in the expression of Nkx3.1 protein. Immunofluorescent antibody localization demonstrated nuclear Nkx3.1 in most bladder cells after PO. We tested if genetic deletion of Nkx3.1 alters remodeling of the bladder wall after PO. After PO, Nkx3.1KO/KO bladders underwent remodeling, demonstrating smaller bladder area, thickness, and bladder: body weight ratios than obstructed, wild type controls. Remarkably, Nkx3.1KO/KO specifically affected histological parameters of fibrosis, including reduced collagen to muscle ratio. Loss of Nkx3.1 altered collagen and smooth muscle cytoskeletal gene expression following PO which supported our histologic findings. Together these findings indicated that after PO, Nkx3.1 expression is induced in the bladder and that it mediates important pathways that lead to tissue fibrosis. As Nkx3.1 is an androgen response gene, our data suggest a possible mechanism by which fibrosis is mediated in male mice and opens the possibility of a molecular pathway mediated by Nkx3.1 that could explain sexual dimorphism in bladder fibrosis.